HADITH QUALITY ANALYSIS OF THE RECOMMENDATION TO STUDY UNTIL CHINA - Shalihah, Raadliyatush; Hamzah, Muhammad Habibi (Tsaqofah : Jurnal Pendidikan Islam, 2021)
This study aims to find out the quality of the hadith of the recommendation to study until China that has been spread and popular among the public. In this research, the method of hadith research is used, which is preceded by takhrij hadith, I'tibar, and analysis in terms of sanad and matan. From the takhrij of the hadith used, this hadith can be found in the book of hadith by Imam Bayhaqi and many scholars of hadith have given assessments. After analyzing the sanad of the hadith, it is found that there is a defect in one of the narrators which makes the hadith a weak hadith.